2002
DOI: 10.1038/sj.bjc.6600629
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-induced anaemia and its potential clinical impact in patients receiving sequential high dose chemotherapy for metastatic testicular cancer

Abstract: First-line sequential high dose chemotherapy is under investigation in patients with 'poor prognosis' metastatic germ cell tumours in order to improve survival. Despite the use of autologous peripheral blood stem cell transplantation and granulocyte colony stimulating factor chemotherapy dose intensification is associated with severe haematotoxicity including anaemia, which may significantly affect quality of life and tolerability of chemotherapy. This study investigates the frequency and degree of anaemia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…The incidence of anemia was as high as 50 to 60% in patients with lung tumors, lymphomas, and genitourinary or gynecologic tumors, and was often higher yet in patients with major solid tumors. Data cited by individual investigators support the findings observed in these larger surveys [22,44,45].…”
Section: Prevalence According To Treatmentsupporting
confidence: 80%
“…The incidence of anemia was as high as 50 to 60% in patients with lung tumors, lymphomas, and genitourinary or gynecologic tumors, and was often higher yet in patients with major solid tumors. Data cited by individual investigators support the findings observed in these larger surveys [22,44,45].…”
Section: Prevalence According To Treatmentsupporting
confidence: 80%
“…The natural history of a disease is dependent on the interaction of both patient and disease factors. Anaemia can be related to the disease process itself, host-related factors or treatment given and has been shown to be associated with significant reduction in survival in various cancers, other than NPC (Caro et al, 2001;Bokemeyer et al, 2002). Anaemia may reflect not only a biologically more aggressive tumour but may be a mediating factor to resistance to treatment and this has been demonstrated in retrospective studies on cervical cancer treated with chemoradiation (Obermair et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the high overall cure rate, interest has shifted from increasing the overall cure rate to reducing treatment-related toxicity for patients with a good prognosis (de Wit et al, 2001). On the other hand, high-risk patients, eligible for more intensive treatment, for example, stem-cell support or high-dose chemotherapy, should be identified (Bokemeyer et al, , 2002.…”
mentioning
confidence: 99%